2018
DOI: 10.1186/s12888-018-1842-4
|View full text |Cite
|
Sign up to set email alerts
|

Attachment, mentalisation and expressed emotion in carers of people with long-term mental health difficulties

Abstract: BackgroundExpressed emotion (EE) is a global index of familial emotional climate, which is comprised of emotional over-involvement (EOI) and critical comments (CC)/hostility. Although EE is an established predictor of negative outcomes for both people with long-term mental health difficulties and their family carers, its psychological underpinnings remain relatively poorly understood. This paper examined associations between attachment, mentalisation ability and aspects of EE.MethodsCarers of people with long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
2
3
0
1
Order By: Relevance
“…This control could result in critical settings in the family, which has a poor impact on disease outcomes. This explanation supports other findings reported by Cherry et al (2018), postulating that EE results from beliefs about the controllability of health-related difficulties. However, previous findings relate controllability as a robust predictor of EE in carers.…”
Section: Discussionsupporting
confidence: 92%
“…This control could result in critical settings in the family, which has a poor impact on disease outcomes. This explanation supports other findings reported by Cherry et al (2018), postulating that EE results from beliefs about the controllability of health-related difficulties. However, previous findings relate controllability as a robust predictor of EE in carers.…”
Section: Discussionsupporting
confidence: 92%
“…Females were found more likely to have a high EE than males and to express a higher level of warmth. This finding, although not statistically significant, is in line with previous results showing that women more often have a high EE [ 53 ] and, in particular, express higher levels of EOI [ 54 ], but at the same time they are more likely to express positive emotions than males and express them more easily [ 55 ]. Most of the study’s female participants were mothers (25/32).…”
Section: Discussionsupporting
confidence: 89%
“…While our study did not find a difference in each component of EE's relationship to mental health, other studies have found that these constructs sometimes function differently in certain contexts. For example, in a sample of carers of people with long-term mental health difficulties, Cherry et al (2018) found that while criticism was related to adult attachment and facets of mentalization, no associations were observed between EOI and adult attachment nor between EOI and mentalization in this sample. In a similar vein, a recent study in early psychosis further found that criticism was more consistently related to relative stress and burden than emotional overinvolvement (Hinojosa-Marqu es, Dom ınguez-Mart ınez, Kwapil, & Barrantes-Vidal, 2019).…”
mentioning
confidence: 65%